Exposure to Low Doses of Biocides Increases Resistance to Other Biocides and to Antibiotics in Strains of Listeria monocytogenes - Cristina Rodríguez-Melcón; Rosa Capita; Carlos Alonso-Calleja (Biology)
The effect of sub-inhibitory doses of three disinfectants, sodium hypochlorite (SHY), peracetic acid (PAA), and benzalkonium chloride (BZK), on the resistance to biocides and antibiotics of five strains of Listeria monocytogenes was determined. The minimum inhibitory concentration (MIC) of these chemicals ranged (ppm) between 3533.3 ± 28.9 and 3783.3 ± 28.9 for SHY, between 1000.0 ± 25.0 and 1050.0 ± 25.0 for PAA, and between 1.3 ± 0.6 and 4.3 ± 0.6 for BZK. The minimum bactericidal concentration (ppm) was between 3683.3 ± 57.7 and 3983.3 ± 28.9 for SHY, between 1050.0 ± 25.0 and 1250.0 ± 25.0 for PAA, and between 1.7 ± 1.2 and 4.7 ± 1.2 for BZK. Exposure of the strains to increasing sub-inhibitory concentrations of the biocides caused adaptation and cross-adaptation to these substances, markedly so in the case of BZK, relative to which some strains saw their MIC value increase up to 5.2 times after being exposed to low doses of this disinfectant. After exposure to biocides, changes in the resistance to antibiotics of the strains were also observed. In some cases, strains moved from a category of susceptible or of reduced susceptibility to resistant, especially when exposure was to SHY. These findings suggest a need to avoid the application of sublethal concentrations of disinfectants in both the food industry and the healthcare system.